2021
DOI: 10.1155/2021/8004883
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Virtual Reality Technology on Clinical Thinking Cultivation of Medical Students

Abstract: Clinical thinking is not only the basis and premise of clinical reasoning and decision-making, but the necessary quality to cultivate reliable, responsible, and emotional excellent doctors. Virtual reality technology provides a real clinical learning environment for medical students, which can bridge the gap between medical theory and medical practice and save educational resources. Virtual reality is helpful to cultivate medical students’ clinical thinking and prepare for their clinical practice. Through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, it is inferior to immersive VRS based on head-mounted VR immersion technology in terms of engagements, interactivity, and enjoyment. China promotes the competency-oriented education and teaching reform, pushes the deep integration of information technology and medical education, cultivates first-class medical talents, and serves the construction of healthy China ( Wang et al, 2021 ). At present, most universities can achieve the goal of desktop VRS teaching, and share the VRS projects on laboratory platform websites designated by the Ministry of Education, even in remote underdeveloped areas of China.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is inferior to immersive VRS based on head-mounted VR immersion technology in terms of engagements, interactivity, and enjoyment. China promotes the competency-oriented education and teaching reform, pushes the deep integration of information technology and medical education, cultivates first-class medical talents, and serves the construction of healthy China ( Wang et al, 2021 ). At present, most universities can achieve the goal of desktop VRS teaching, and share the VRS projects on laboratory platform websites designated by the Ministry of Education, even in remote underdeveloped areas of China.…”
Section: Discussionmentioning
confidence: 99%
“…Today in the information age, multi-domain integration research has become a research priority in many disciplines. Some researchers have applied virtual reality technologies to immersive learning, healthcare, machine learning, meta-universe fields, and more [52][53][54][55]. For example, learning in an immersive virtual reality environment has resulted in far more effective learning than traditional teaching.…”
Section: Multi-disciplinary Integration Researchmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Influence of Virtual Reality Technology on Clinical Thinking Cultivation of Medical Students” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled "Infuence of Virtual Reality Technology on Clinical Tinking Cultivation of Medical Students" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%